A high wear-resistant hard alloy composite material and preparation method thereof
By reasonably mixing tungsten carbide and titanium carbide in cemented carbide, and preparing bonded phases in combination with electrochemical methods, and using multi-process processing methods, the problem of difficult to take into account between mechanical properties and wear resistance of cemented carbide materials is solved, and a comprehensive improvement of high hardness, good toughness and excellent wear resistance is achieved.
Patent Information
- Application Number
- CN202510089039.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The existing cemented carbide materials are difficult to balance between mechanical properties and wear resistance, and have poor toughness and insufficient wear resistance, which limits their further development in industrial applications.
By mixing tungsten carbide with titanium carbide in a specific mass ratio and heat treatment, a hard phase is formed; at the same time, the bonded phase is prepared by electrochemical methods, and treated by ball milling, pressing, discharge plasma sintering, annealing and other processes, the mass ratio and treatment conditions of the hard phase and the bonded phase are reasonably adjusted to improve the hardness and toughness of the alloy.
The high hardness and good impact toughness of cemented carbide are achieved, while improving its wear resistance and significantly improving its comprehensive mechanical properties.
Smart Images

Figure CN119506639B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hard alloy material preparation, in particular to a high wear-resistant hard alloy composite material and a preparation method thereof. Background Art
[0002] Cemented carbide materials are widely used in various high-wear-resistant industrial technology fields such as cutting tools and molds due to their high hardness, high strength, good high-temperature performance and excellent wear resistance.
[0003] Traditional cemented carbide is generally prepared using powder metallurgy technology, which uses carbides of high-hardness refractory metals such as WC as the main phase component, and adds binding phases such as cobalt or nickel. It is pressed into shape and then sintered. The resulting cemented carbide can ensure high hardness, but has poor toughness and high brittleness, making it difficult to process and prone to fracture when impacted, which seriously hinders the further research and application of cemented carbide.
[0004] In order to solve the above technical problems, the prior art proposes to use cemented carbide and other nucleating agents as materials to improve toughness, to compound them to improve the performance of cemented carbide, and to improve the comprehensive performance of cemented carbide by coating functional coatings such as titanium nitride and aluminum oxide on the surface of cemented carbide. However, the prior art mainly adopts chemical vapor deposition or physical vapor deposition to coat the functional coating on the surface of cemented carbide, which is easily affected by the environment during use, resulting in poor bonding ability between the coating and the substrate, and cannot effectively and stably improve the mechanical properties of cemented carbide.
[0005] In the prior art, cemented carbide materials are compounded with carbon steel materials to improve the comprehensive mechanical properties of the alloy. Carbon steel materials and cemented carbide materials are mainly combined using welding technology. However, the physical and chemical differences between cemented carbide and carbon steel materials are large, resulting in insufficient strength of the welding part, forming a carbon-poor layer on one side of the cemented carbide, resulting in a large amount of thermal residual stress in the welding part, high brittleness at the weld, and poor wear resistance at the weld, which limits the further use of cemented carbide.
[0006] In summary, the prior art still has obvious shortcomings in improving the performance of cemented carbide, and cemented carbide still has the problem that mechanical properties and wear resistance cannot be satisfied at the same time.
[0007] To this end, the present invention provides a high wear-resistant cemented carbide composite material and a preparation method thereof. Summary of the invention
[0008] The invention aims to provide a high wear-resistant cemented carbide composite material and a preparation method thereof. The method comprises the following steps: uniformly mixing tungsten carbide and titanium carbide in a mass ratio and subjecting the mixture to heat treatment to obtain a hard phase; dissolving nickel sulfate hexahydrate, sodium molybdate dihydrate and nanoparticles in a solvent as a cathode and subjecting the mixture to electrochemical treatment to obtain a bonding phase; subjecting the hard phase and the bonding phase to ball milling, pressing, discharge plasma sintering, annealing treatment, grinding and cleaning to obtain the high wear-resistant cemented carbide; controlling the temperature, time and cooling time of the heat treatment to avoid excessive growth of hard phase grains and improve the hardness of the alloy; adjusting the current density and solution temperature during the electrochemical reaction to improve the amount of molybdenum element and improve the toughness of the alloy; controlling the mass ratio of the hard phase to the bonding phase, adjusting the temperature and time of the discharge plasma sintering, and improving the hardness and transverse rupture strength of the alloy; further adjusting the grain size of the cemented carbide by controlling the annealing time and temperature to improve the comprehensive mechanical properties of the alloy; and controlling the type, amount and size of the nanoparticles to improve the hardness of the alloy and the wear resistance.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] The present invention provides a method for preparing a high wear-resistant cemented carbide composite material, wherein the preparation of the high wear-resistant cemented carbide composite material comprises the following steps:
[0011] S1: grinding and mixing tungsten carbide and titanium carbide, and pressing and molding to obtain a mixed body; heat treating the mixed body, and cooling it to room temperature with an argon gas flow to obtain a hard phase;
[0012] S2: adding nickel sulfate hexahydrate, sodium molybdate dihydrate and nanoparticles to a mixed solvent for dispersion and dissolution, and ultrasonically treating to obtain an ultrasonic solution; using the ultrasonic solution as an electroplating solution for electroplating to obtain an electroplated sample; and washing and drying the electroplated sample to obtain a bonding phase;
[0013] S3 ball-milling the hard phase and the binder phase to obtain a mixed alloy; pressing the mixed alloy into a shape to obtain an alloy blank; sintering the alloy blank, cooling it in a nitrogen atmosphere to obtain a cooled alloy; annealing the cooled alloy, and naturally cooling it to room temperature to obtain a treated alloy; polishing, cleaning, and vacuum drying the treated alloy to obtain the high wear-resistant cemented carbide composite material;
[0014] The ball-to-material ratio in the ball milling process is 6:1, the ball milling speed is 600 rpm, and the ball milling time is 12 h.
[0015] The mixed solvent is formed by mixing sodium sulfate and sodium citrate in a volume ratio of 1:1;
[0016] The mass ratio of the hard phase to the binding phase is 3-9:1-3;
[0017] The sintering treatment is selected from one of microwave sintering and spark plasma sintering;
[0018] The size of the nanoparticles is 0.5nm-100nm;
[0019] The concentration of the sodium molybdate dihydrate is 1-8 g / L.
[0020] The preferred ball milling method can control the size of the alloy grains. The present invention controls the size of the hard phase grains by heat treating tungsten carbide and titanium carbide and adjusting the temperature and time. The bonding phase grain size obtained by the electrochemical method is uniform, while avoiding excessive grain growth. During the ball milling process, further growth of the grains is avoided.
[0021] Preferably, the heat treatment temperature is 1250-1400° C., and the time is 2-5 hours; and the argon flow cooling time is 30-90 minutes.
[0022] Preferably, the preparation of the binder phase comprises the following steps:
[0023] The nickel sulfate hexahydrate and the sodium molybdate dihydrate are added to the mixed solvent, and stirred to uniformly dissolve to obtain the mixed solution; the nanoparticles are added to the mixed solution to fully disperse, and ultrasonicated for 30 minutes to obtain the ultrasonic solution; the ultrasonic solution is added to a beaker, and the beaker is placed in a constant temperature water bath, and a pure nickel plate is used as an anode, and the ultrasonic solution is used as an electroplating solution for electroplating to obtain an electroplated sample; the electroplated sample is taken out, ultrasonically cleaned for 20 minutes, and vacuum dried to obtain the bonding phase;
[0024] The water bath temperature is 30-60°C; the current density of the electroplating treatment is 3-6A / dm 2 .
[0025] Preferably, the concentration of the nickel sulfate hexahydrate is 12 g / L; the concentration of the sodium molybdate dihydrate is 2-5 g / L.
[0026] Preferably, the nanoparticles are selected from one of nano-alumina, nano-silicon dioxide and nano-titanium dioxide.
[0027] Preferably, the mass percentage of the nanoparticles in the binder phase is 8%-20%; and the size of the nanoparticles is 2.5nm-20nm.
[0028] Preferably, the microwave sintering comprises the following steps:
[0029] The alloy blank is placed in a microwave sintering furnace, the sintering temperature is controlled to be 1200-1800° C. under high-purity argon conditions, the sintering time is 30-60 min, and it is naturally cooled to room temperature under nitrogen atmosphere conditions to obtain the cooled alloy.
[0030] Preferably, the spark plasma sintering comprises the following steps:
[0031] The alloy blank is placed in a spark plasma sintering furnace, the sintering temperature is controlled to be 1200-1800° C. under high-purity argon conditions, the sintering time is 5-15 minutes, and it is naturally cooled to room temperature under nitrogen atmosphere conditions to obtain the cooled alloy.
[0032] Preferably, the temperature of the annealing treatment is 900-1200° C.; the time of the annealing treatment is 2-3.5 hours.
[0033] The present invention also provides a high wear-resistant cemented carbide composite material prepared by the method as described above, wherein the high wear-resistant cemented carbide composite material comprises a hard phase and a bonding phase; the hard phase comprises tungsten carbide and titanium carbide, and the bonding phase comprises nickel sulfate hexahydrate, sodium molybdate dihydrate and nanoparticles.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention mixes tungsten carbide and titanium carbide uniformly, utilizes the fact that tungsten carbide grains grow with the extension of temperature and time during heat treatment, and the formation of uneven grains causes the hardness of the alloy to be significantly reduced. By controlling the heat treatment temperature and time, and controlling the cooling rate, the hardness and impact toughness of the prepared cemented carbide are significantly improved.
[0036] 2. By using an electrochemical method, metal nickel and metal molybdenum are combined in the form of a solid solution, and nanoparticles are added at the same time. By controlling the current density and the temperature of the electroplating solution, the amount of molybdenum element in the obtained bonding phase is controlled, thereby improving the bonding ability between the bonding phase and the hard phase. At the same time, the addition of the bonding phase improves the toughness of the cemented carbide and improves the comprehensive mechanical properties.
[0037] 3. The present invention ball-mills the hard phase and the binder phase to avoid agglomeration between metal alloy particles, utilizes the binder phase atoms to promote the diffusion of the hard phase atoms, accelerates the grain growth, and improves the densification degree of the cemented carbide. When using spark plasma sintering, a graphite sintering vessel is selected to increase the carbon potential in the furnace chamber, avoid the occurrence of decarburization reaction, and further improve the mechanical properties of the alloy.
[0038] 4. The present invention utilizes the hard phase and the binder phase to dissolve into a uniformly distributed β phase during annealing treatment, and at the same time a uniformly dispersed second phase is precipitated, so that the grain structure is refined, the hardness and toughness of the alloy are further improved, the annealing temperature and time are controlled, and the mechanical properties of the alloy are further improved.
[0039] 5. The present invention utilizes nanoparticles to provide more nucleation cores and hinder the growth of crystals, thereby refining the grains of the alloy, increasing the volume fraction of the grain boundaries, and further improving the hardness of the alloy. At the same time, the size of the nanoparticles is controlled to improve the wear resistance of the cemented carbide. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The present invention is a process flow chart for preparing a highly wear-resistant cemented carbide composite material. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] See also Figure 1 The present invention provides a high wear-resistant cemented carbide composite material and a preparation method thereof, and the technical scheme is as follows:
[0043] Example 1
[0044] Preparation of mixed powder:
[0045] Mechanically grinding and mixing tungsten carbide and titanium carbide at a mass ratio of 1:1 to obtain a mixed powder; pressing the mixed powder to obtain a mixed green body; heat treating the mixed green body at 1250° C. for 3 hours, and cooling to room temperature within 60 minutes to obtain a hard phase;
[0046] 15 g / L nickel sulfate hexahydrate and 4 g / L sodium molybdate dihydrate were added to a mixed solution of sodium sulfate and sodium citrate (solvent volume ratio 1:1), and stirred to dissolve evenly to obtain a mixed solution; nano-alumina was added to the mixed solution to fully disperse it, and placed in an ultrasonic instrument for ultrasonication for 30 minutes to obtain an ultrasonic solution; the ultrasonic solution was added to a beaker, and the beaker was placed in a 50°C constant temperature water bath, a pure nickel plate was used as an anode, and the ultrasonic solution was used as an electroplating solution for electroplating, and the power was turned on to maintain a current density of 5A / dm 2During the electroplating process, the sample was stirred to eliminate hydrogen bubbles on the surface, and the electroplating process was performed for 1 hour to obtain an electroplated sample; the electroplated sample was taken out, ultrasonically cleaned for 20 minutes, and vacuum dried at 60° C. for 30 minutes to obtain a bonding phase;
[0047] The hard phase and the binder phase are added to a planetary ball mill and ball milled for 12 hours to obtain a mixed alloy, the ball-to-material ratio of the ball milling is 6:1, and the ball milling speed is 600 rpm; the mixed alloy is pressed into shape to obtain an alloy blank; the alloy blank is subjected to spark plasma sintering treatment, kept at 1600°C for 10 minutes, and then cooled in a nitrogen atmosphere for 60 minutes to obtain a cooled alloy; the cooled alloy is annealed at 1100°C for 3 hours, and naturally cooled to room temperature to obtain a treated alloy; the treated alloy is polished by sandpaper, cleaned with deionized water, and vacuum dried to obtain the high wear-resistant cemented carbide. Figure 1 This is a flow chart for preparing the highly wear-resistant cemented carbide composite material obtained in Example 1 of the present invention.
[0048] Example 2-11 The preparation method and parameter conditions of Example 1 are referred to, and the differences are shown in Table 1.
[0049] Comparative Example 1 The preparation method and parameter conditions are the same as those of Example 1, except that titanium carbide is not added.
[0050] Comparative Example 2 The preparation method and parameter conditions are the same as those of Example 1, except that no heat treatment is performed.
[0051] Example 12 Hardness Test
[0052] The high wear-resistant cemented carbides prepared in Examples 1-11 and Comparative Examples 1-2 were tested for Rockwell hardness using a digital Rockwell hardness tester (Xi'an Huayin Instruments Co., Ltd.) in accordance with GB / T 3849.1-2015 standard, and the impact toughness of the cemented carbides was tested using a pendulum impact tester in accordance with GB / T 1817-2017. The test results are shown in Table 1.
[0053] Table 1 Hardness test of Examples 1-11 and Comparative Examples 1-2
[0054]
[0055] From the results in Table 1, it can be seen that the hard phase obtained in Comparative Example 1 without adding titanium carbide has a significantly lower hardness than that of Examples 1-11, reaching only 85HRA. Since titanium carbide can hinder the growth of grains to a certain extent, it will be concentrated on the grain boundaries, forming a "drag" effect that hinders the migration of grain boundaries and avoids the further growth of tungsten carbide grains. At the same time, the overall particle size of titanium carbide is larger than that of tungsten carbide. It is evenly dispersed in tungsten carbide during mechanical grinding and forms a hard phase of (Ti, W) C during heat treatment, which inhibits the dissolution of WC and enhances the hardness of the alloy. The hardness of the alloy obtained without heat treatment in Comparative Example 2 is also significantly reduced. Since a solid solution hard phase cannot be formed, the overall hardness of the alloy is reduced. From the results of Examples 1-4, it can be seen that with the increase of heat treatment temperature, the hardness of the alloy The hardness gradually decreases because at high temperatures, tungsten carbide grains will grow with time. At the same time, too high a temperature will further reduce the uniformity of grain formation. The formation of uneven grains causes the hardness of the alloy to be significantly reduced. The results of Example 2 and Example 5-11 show that with the extension of heat treatment time, the hardness of the alloy is significantly reduced. Due to the extension of time, the growth of grains is more obvious. By reducing the heat treatment time and the cooling time, the promotion of high temperature on the growth of tungsten carbide alloy grains is reduced, and the hardness of the alloy is further improved. However, too short cooling time and heat treatment time further affect the toughness of the alloy, and the overall mechanical properties are reduced. By adjusting the temperature, treatment time and cooling time during the heat treatment of the hard phase, the overall mechanical properties of the alloy are improved.
[0056] Embodiment 13
[0057] 15 g / L nickel sulfate hexahydrate and 4 g / L sodium molybdate dihydrate were added to a mixed solution of sodium sulfate and sodium citrate (solvent volume ratio 1:1), and stirred to dissolve evenly to obtain a mixed solution; nano-alumina was added to the mixed solution to fully disperse it, and placed in an ultrasonic instrument for ultrasonication for 30 minutes to obtain an ultrasonic solution; the ultrasonic solution was added to a beaker, and the beaker was placed in a 50°C constant temperature water bath, a pure nickel plate was used as an anode, and the ultrasonic solution was used as an electroplating solution for electroplating, and the power was turned on to maintain a current density of 5A / dm 2 During the electroplating process, the sample was stirred to eliminate hydrogen bubbles on the surface. After electroplating for 1 hour, an electroplated sample was obtained. The electroplated sample was taken out, ultrasonically cleaned for 20 minutes, and vacuum dried at 60° C. for 30 minutes to obtain a bonding phase. The cemented carbide was prepared according to Example 2.
[0058] Examples 14-23 The preparation methods and parameter conditions of Example 13 are referred to, with the differences shown in Table 2.
[0059] Comparative Example 3 The preparation method and parameter conditions are the same as those of Example 13, except for the bonding phase.
[0060] Example 24 Toughness Test
[0061] The toughness of the alloys of Examples 13-23 and Comparative Example 3 was tested using an electronic universal testing machine in accordance with GB / T3851-2015, and the transverse rupture strength of the cemented carbide was calculated using the three-point test bending resistance formula. The test results are shown in Table 2.
[0062] Table 2 Toughness test of Examples 13-23 and Comparative Example 3
[0063]
[0064] From the results in Table 2, it can be seen that the flexural strength of the cemented carbide prepared without adding a binder phase in Comparative Example 3 is significantly lower than that of Examples 13-23, and the hardness of the binder phase is lower than that of the hard phase. However, the nano-alumina introduced into the binder phase is more tightly bonded to the hard phase, and the pinning effect is obvious, which makes the phase change toughening effect more significant. At the same time, when the cracks encounter the binder phase particles during expansion, the toughening mechanisms such as deflection, bridging and micro-cracks occur, which greatly improves the toughness. From the results of Examples 13-23, it can be seen that changes in current density, solution temperature, and sodium molybdate concentration will lead to changes in the molybdenum content in the binder phase, thereby affecting the overall toughness of the cemented carbide. When the content of Mo is low, since the atomic radius of Mo is larger than that of Ni and Al, the Mo atoms occupying the lattice position in the bonding phase will cause serious lattice distortion, so its solid solution strengthening mechanism is dominant at this time, so that the fracture toughness and hardness of the alloy are significantly enhanced. However, when the molybdenum content exceeds the solid solubility limit of the cemented carbide, many intermetallic compounds will be produced, which will further reduce the flexural strength of the cemented carbide with a large molar ratio of added molybdenum. It can be seen from the results of Examples 13-23 that controlling the current density, solution temperature and sodium molybdate concentration of the electrochemically generated bonding phase can effectively improve the flexural strength of the cemented carbide and significantly improve the toughness.
[0065] Embodiment 25
[0066] The synthesis of the hard phase and the binder phase was prepared by referring to Example 16;
[0067] The hard phase and the binder phase are added to a planetary ball mill and ball milled for 12 hours to obtain a mixed alloy, the ball-to-material ratio of the ball milling is 6:1, and the ball milling speed is 600 rpm; the mixed alloy is pressed into shape to obtain an alloy blank; the alloy blank is sintered at a spark plasma sintering temperature of 1600°C for 10 minutes, and cooled in a nitrogen atmosphere for 60 minutes to obtain a cooled alloy; the cooled alloy is annealed at 1100°C for 3 hours, and naturally cooled to room temperature to obtain a treated alloy; the treated alloy is polished by sandpaper, cleaned with deionized water, and vacuum dried to obtain the high wear-resistant cemented carbide.
[0068] Examples 26-37 The preparation methods and parameter conditions of Example 25 are referred to, with the differences shown in Table 3.
[0069] Table 3 Parameter changes of Examples 25-37
[0070]
[0071] Example 38 Mechanical Properties Determination
[0072] The Rockwell hardness of the cemented carbide of Examples 25-37 was measured according to GB / T 3849.1-2015 standard, and the bending strength of the cemented carbide was measured according to GB / T3851-2015. The test results are shown in Table 4.
[0073] Table 4 Mechanical properties of Examples 25-37
[0074]
[0075] The results in Table 4 show that in Examples 25-28, by changing the mass ratio of the hard phase and the binder phase, the hardness and toughness of the cemented carbide are significantly changed. With the increase in the amount of the binder phase, the hardness shows a trend of gradually decreasing, and the transverse fracture strength shows a trend of gradually increasing. As the amount of the binder phase increases, the chances of contact between adjacent binder phase particles also increase, thereby merging and growing; however, since the binder phase atoms can promote the diffusion of the hard phase atoms to accelerate the grain growth and improve the densification of the cemented carbide, the hardness gradually increases; but too much binder phase distributed at the tungsten carbide grain boundary will produce a pinning effect, making the phase transformation toughening effect more significant, and the flexural strength is greatly improved; the results of Examples 29-32 show that by changing the microwave sintering time, the hardness and flexural strength of the alloy show a trend of first increasing and then decreasing, compared with the release The overall mechanical properties of electric plasma are poor. After pretreatment, the tungsten carbide grains and the binder phase grains appear as particle agglomerates similar to the powder form, and the grain boundaries between the particles are blurred. There are many pores in the material, resulting in low density. As the temperature rises, some pores are eliminated, the densification degree of the material increases, and the grain size continues to coarsen when the sintering temperature increases. The grain size grows abnormally, and there are no small grains around the large pores to fill, the density decreases, and the hardness and fracture toughness also decrease accordingly. However, due to the characteristics of the microwave electromagnetic field and the use of different insulation materials and contact materials during sintering, the environmental carbon potential in the microwave sintering cavity cannot be increased, and decarburization occurs during the sintering process. Graphite sintering vessels are selected for discharge plasma sintering, which can increase the carbon potential in the furnace cavity and avoid the occurrence of decarburization reactions, showing a decrease in hardness and toughness.
[0076] Examples 39-46 The preparation methods and parameter conditions of Example 26 are referred to, with the differences shown in Table 5.
[0077] Comparative Example 4 The preparation method and parameter conditions are the same as those of Example 26, except that no annealing treatment is performed.
[0078] Example 47 Mechanical Properties Determination
[0079] The Rockwell hardness of the cemented carbide of Examples 39-46 and Comparative Example 4 was measured according to GB / T3849.1-2015 standard, and the bending strength of the cemented carbide was measured according to GB / T3851-2015. The test results are shown in Table 5.
[0080] Table 5 Mechanical properties of Examples 39-46 and Comparative Example 4
[0081]
[0082] From the results in Table 5, it can be seen that the hardness of the cemented carbide obtained without annealing in Comparative Example 4 can meet the basic requirements of the alloy, but the transverse rupture strength is significantly lower than that of Examples 39-46, and the poor toughness affects the further use of the alloy; from the results of Examples 39-42, it can be seen that with the increase of annealing temperature, the hardness of the cemented carbide shows a trend of first increasing and then decreasing, while the transverse rupture strength shows a gradual increase. With the increase of annealing temperature, the hard phase and the bonding phase are dissolved into a uniformly distributed β phase, and a uniformly dispersed second phase is precipitated, which enhances the degree of grain refinement and further improves the hardness and toughness of the alloy. However, with the continued increase in temperature, the rearrangement of the grains will cause the carbide particles in the cemented carbide to coarsen, the grains to grow, and the cemented carbide Hardness, and high temperature annealing will also promote the uniform distribution of the bonding phase, but the increase or redistribution of the bonding phase will also reduce the overall hardness; from the results of Examples 41 and 43-46, it can be seen that with the increase of annealing time, the hardness of the cemented carbide shows a trend of first increasing and then decreasing, while the transverse rupture strength shows a gradual increase, and the eutectic second phase precipitates, which has a certain weakening effect on toughness while improving the strength. With the extension of annealing time, the distribution of the eutectic second phase tends to be uniform, which improves the toughness of the cemented carbide. However, the extension of annealing time will lead to significant grain growth, reducing the hardness and toughness of the alloy; In summary, by controlling the annealing temperature and annealing time, the Rockwell hardness of the obtained cemented carbide is 92HRA, and the transverse rupture strength is 3650MPa, showing significantly improved comprehensive mechanical properties.
[0083] Examples 48-57 Refer to the preparation method and parameter conditions of Example 41, with the differences as shown in Table 6.
[0084] Comparative Example 5
[0085] The hard phase prepared in Example 41 is used, and the hard phase, metal nickel, metal molybdenum, and nano-titanium dioxide are added to a planetary ball mill for ball milling for 12 hours to obtain a mixed alloy, the ball-to-material ratio of ball milling is 10:1, and the ball milling speed is 800 rpm; the mixed alloy is pressed into shape to obtain an alloy blank; the alloy blank is sintered at a sintering temperature of 1600°C for 10 minutes, and cooled in a nitrogen atmosphere for 60 minutes to obtain a cooled alloy; the cooled alloy is annealed at 1100°C for 3 hours, and naturally cooled to room temperature to obtain a treated alloy; the treated alloy is polished by sandpaper, cleaned with deionized water, and vacuum dried to obtain the high wear-resistant cemented carbide.
[0086] Comparative Example 6 The preparation method and parameter conditions are the same as those of Example 41, except that no nanoparticles are added.
[0087] Example 58 Wear resistance test
[0088] The high wear-resistant cemented carbides prepared in Examples 48-57 and Comparative Examples 5-6 were subjected to wear test according to the test method of GBT 34501-2017. The test results are shown in Table 6.
[0089] Table 6 Wear test of Examples 48-57 and Comparative Examples 5-6
[0090]
[0091] The results in Table 6 show that in Comparative Example 5, the volume wear amount of the cemented carbide obtained by adding the bonding phase by grinding and blending is significantly improved compared with Examples 48-57, and the friction resistance is poor. The bonding phase obtained by electrochemistry can limit the grain growth of the bonding phase by controlling the current density and temperature, thereby avoiding excessive growth of the grains and reducing the strength of the alloy. In the grinding and blending process, the nanoparticles in the bonding phase are used to enhance the effect through their own nano-size effect. At the same time, the introduction of nano-titanium dioxide increases the bonding ability with the tungsten carbide matrix, forms a solid solution phase to avoid further growth of the grains, and improves the wear resistance of the alloy. In Comparative Example 6, no nanoparticles are added, the growth of the alloy grains cannot be restricted, the grains are too large, affecting the hardness of the alloy, and then reducing the wear resistance. The results of Examples 50-53 show that the addition of nanoparticles can provide more nucleation cores and hinder the growth of crystals, so that the grains of the alloy Refinement, increase the volume fraction of grain boundaries; the dislocations of the alloy will slip and increase along certain crystal planes, and this slipping dislocation is blocked at the grain boundary, thereby forming a dislocation pile-up inside the crystal to increase the hardness of the coating, and with the increase in dosage, the volume wear of the alloy shows a trend of gradually decreasing; the results of Examples 50, 54-57 show that with the increase in the size of the nanoparticles, the volume wear of the alloy shows a trend of first decreasing and then increasing. When the particle size is much smaller than the grain size, the particles can be completely coated in the crystal. At this time, the moving dislocations will be hindered by the particles to generate friction, and the wear resistance will deteriorate. When the particle size is larger than the grain size, the particles are squeezed to the outside of the crystal, and it is difficult for the hard phase to achieve complete coating of all particles. A part of the large particles are taken away from the alloy surface under the action of friction, thereby increasing friction and increasing volume wear; by controlling the dosage and size of the nanoparticles, the wear resistance of the alloy is further improved.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a highly wear-resistant cemented carbide composite material, characterized in that: The preparation of the highly wear-resistant cemented carbide composite material comprises the following steps: S1: grinding and mixing tungsten carbide and titanium carbide, and pressing and molding to obtain a mixed body; heat treating the mixed body, and cooling it to room temperature with an argon gas flow to obtain a hard phase; The heat treatment temperature is 1250-1400°C, the heat treatment time is 2-5h; the argon gas flow cooling time is 30-90min; S2: adding nickel sulfate hexahydrate, sodium molybdate dihydrate and nanoparticles to a mixed solvent for dispersion and dissolution, and ultrasonically treating to obtain an ultrasonic solution; using the ultrasonic solution as an electroplating solution for electroplating to obtain an electroplated sample; and washing and drying the electroplated sample to obtain a bonding phase; S3 ball-milling the hard phase and the binder phase to obtain a mixed alloy; pressing the mixed alloy into a shape to obtain an alloy blank; sintering the alloy blank, cooling it in a nitrogen atmosphere to obtain a cooled alloy; annealing the cooled alloy, and naturally cooling it to room temperature to obtain a treated alloy; polishing, cleaning, and vacuum drying the treated alloy to obtain the high wear-resistant cemented carbide composite material; The ball-to-material ratio in the ball milling process is 6:1, the ball milling speed is 600 rpm, and the ball milling time is 12 h. The mixed solvent is formed by mixing sodium sulfate and sodium citrate in a volume ratio of 1:1; The mass ratio of the hard phase to the binding phase is 3-9:1-3; The sintering treatment is selected from one of microwave sintering and spark plasma sintering; The size of the nanoparticles is 0.5nm-100nm; The concentration of the sodium molybdate dihydrate is 1-8 g / L.
2. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 1, characterized in that: The preparation of the bonding phase comprises the following steps: The nickel sulfate hexahydrate and the sodium molybdate dihydrate are added to the mixed solvent, and stirred to uniformly dissolve to obtain a mixed solution; the nanoparticles are added to the mixed solution to fully disperse, and ultrasonicated for 30 minutes to obtain the ultrasonic solution; the ultrasonic solution is added to a beaker, and the beaker is placed in a constant temperature water bath, and a pure nickel plate is used as an anode, and the ultrasonic solution is used as an electroplating solution for electroplating to obtain an electroplated sample; the electroplated sample is taken out, ultrasonically cleaned for 20 minutes, and vacuum dried to obtain the bonding phase; The water bath temperature is 30-60°C; the current density of the electroplating treatment is 3-6A / dm 2 .
3. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 2, characterized in that: The concentration of the nickel sulfate hexahydrate is 12 g / L; the concentration of the sodium molybdate dihydrate is 2-5 g / L.
4. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 2, characterized in that: The nanoparticles are selected from one of nano-alumina, nano-silicon dioxide and nano-titanium dioxide.
5. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 2, characterized in that: The mass percentage of the nanoparticles in the binder phase is 8%-20%; the size of the nanoparticles is 2.5nm-20nm.
6. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 1, characterized in that: The microwave sintering comprises the following steps: The alloy blank is placed in a microwave sintering furnace, the sintering temperature is controlled to be 1200-1800° C. under high-purity argon conditions, the sintering time is 30-60 min, and it is naturally cooled to room temperature under nitrogen atmosphere conditions to obtain the cooled alloy.
7. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 1, characterized in that: The spark plasma sintering comprises the following steps: The alloy blank is placed in a spark plasma sintering furnace, the sintering temperature is controlled to be 1200-1800° C. under high-purity argon conditions, the sintering time is 5-15 minutes, and it is naturally cooled to room temperature under nitrogen atmosphere conditions to obtain the cooled alloy.
8. The method for preparing a highly wear-resistant cemented carbide composite material according to claim 1, characterized in that: The temperature of the annealing treatment is 900-1200° C.; the time of the annealing treatment is 2-3.5 hours.
9. A highly wear-resistant cemented carbide composite material prepared by the method of claim 1, characterized in that: The high wear-resistant cemented carbide composite material comprises a hard phase and a bonding phase; the raw materials of the hard phase are tungsten carbide and titanium carbide, and the raw materials of the bonding phase are nickel sulfate hexahydrate, sodium molybdate dihydrate and nanoparticles.
Citation Information
Patent Citations
Nano-particle modified titanium-carbide-based hard alloy and preparation method thereof
CN105861905A
Carbide composition and procedure for making
GB807769A
High-toughness hard alloy and its manufacturing method
JP2003155537A